Financial Performance Of Bumdes Maju Bersama, Durian Sebatang Village, South Bengkulu Regency - Cindy Ramadani; Kresnawati Kresnawati; Iswidana Utama Putra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
The purpose of this study is to determine the financial performance of BUMDes Maju Bersama in Durian Sebatang Village, South Bengkulu Regency, during the 2022–2024 period. This research uses an explanatory research method. The results of the study show that the Liquidity Ratio (Current Ratio): BUMDes Durian Sebatang Village shows that the company's liquidity condition has increased from 1.33 in the year of 1999 with poor criteria, in 2023 to 1.53 quite good, in 2024 to 1.62 with fairly good criteria. Activity Ratio: Total Assets Turnover shows an increase in the efficiency of asset use in 2022 by 3.04% with good criteria, in 2023 by 6.76% with very good criteria and in 2024 by 12.7 with very good criteria. Solvency Ratio: Debt to Equity Ratio (DER) of BUMDes is 0% during 2022-2024, indicating that BUMDes is fully funded by equity and does not rely on debt, Profitability Ratio: Net Profit Margin (NPM) shows the calculation results for 2022 of 3.4% with less criteria, in 2023 of 6.8% with sufficient criteria, and in 2024 of 1.3% with very less criteria. Return on Equity (ROE): shows the standard results of Return On Equity (ROE) calculations from 2022-2024, the calculation results for 2022 of 3.4% with very less criteria, in 2023 of 7.13% with less criteria, and in 2024 of 7.5% with less criteria. Return on Assets (ROA) shows the standard results of the Return on Assets (ROA) calculation from 2022 to 2024. The calculation results for 2022 were 3%, which is considered inadequate, in 2023 it was 6%, which is considered adequate, and in 2024 it was 1%, which is considered very inadequate.